Between compassionateness and assertiveness: A trust matrix for leaders - Victor Manuel Monteiro Seco; Miguel Pereira Lopes (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: Construct the structure of trust-building perceived by principals in Portuguese public schools. Design/methodology/approach: A grounded theory approach applied to a survey of open questions answered by school's principals. Findings: (1) self-trust is the single trait common to all respondents; (2) compassion is a striking antecedent in the process of other-trust; compassionateness and assertiveness must combine with one another to achieve leadership based on smart trust, what is outlined in a matrix model built from the data. Research limitations/implications: The major limitation of this study was the impossibility to conduct face-to-face interviews given the limitation of free time alleged by the principals. In order to solve that limitation we decide to use the grounded theory approach. Practical implications: The consideration of a symbiosis category of the behaviors of principals can trigger positive expectations among the players who until now did not understand how it is possible to bring together the best of the worlds of management and leadership in a balanced way, with efficiency in authenticity. Social implications: The aforementioned dyadic model reflects a psychological state based on the belief that others do not take advantage of us, showing that trust is an essential element in positive human relations and becomes a strategic issue. Originality/value: The present study found that "pure" positive behaviors, as being compassionate, might need to be tempered or complemented with other behaviors such as assertiveness, to become really effective.
Keywords: 650; leadership; trust; self and other trust; compassionateness; assertiveness